2018
DOI: 10.1007/s13224-018-1119-3
|View full text |Cite
|
Sign up to set email alerts
|

Dienogest Versus Leuprolide Acetate for Recurrent Pelvic Pain Following Laparoscopic Treatment of Endometriosis

Abstract: Daily dienogest is as effective as depot LA for relieving endometriosis-associated pelvic pain, low back pain and dyspareunia. In addition, dienogest has acceptable safety, tolerability and lower incidence of hot flushes. Thus, it may offer an effective and well-tolerated treatment in endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
1
4
0
1
Order By: Relevance
“…Also, after collecting the side effects of the medication, it was found that hypoestrogenism, such as cramps and spotting, was more in the first group; Endogenous complications such as oily skin, acne, and hirsutism were also more common in the second group. Numerous previous studies have confirmed these findings (7,8,25,26).…”
Section: Evaluation Of Mif Gene Expressionsupporting
confidence: 62%
See 1 more Smart Citation
“…Also, after collecting the side effects of the medication, it was found that hypoestrogenism, such as cramps and spotting, was more in the first group; Endogenous complications such as oily skin, acne, and hirsutism were also more common in the second group. Numerous previous studies have confirmed these findings (7,8,25,26).…”
Section: Evaluation Of Mif Gene Expressionsupporting
confidence: 62%
“…Therefore, one of the ways to treat endometriosis is to use GnRH agonist drugs that inhibit estrogen production (6). Leuprolide acetate is a synthetic nonapeptide analogue of the gonadotropin-releasing hormone (GnRH or LH-RH) (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, 55 of them did not meet the inclusion criteria. Ultimately, we involved 16 articles in our network meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…Dienogest is currently under investigation as an alternative long-term treatment. 24,25 Gestagens create false signals of pregnancy, thereby blocking estrogen and subsequently mucosa and cyst growth. A contraceptive Dienogest coil can also be used.…”
Section: Discussionmentioning
confidence: 99%